2010
DOI: 10.1007/s13277-010-0068-y
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological significance of E-cadherin, VEGF, and MMPs in gastric cancer

Abstract: E-cadherin, vascular endothelial growth factor (VEGF), and matrix metalloproteinases (MMPs) are important molecules involved in tumor metastasis. In this study, we examined the expressions of E-cadherin, VEGF, MMP-1, MMP-2, and microvessel density (MVD), as well as microlymphatic vessel density (MLVD) in 200 cases of gastric cancer tissues, and determined the relationship between these parameters and the clinicopathological features and patient survival. Protein expressions, MVD, and MLVD were detected by immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 19 publications
0
30
0
6
Order By: Relevance
“…Apparently, early diagnosis of its recurrence and metastasis is the biggest challenge in improving the survival of patients with GC. Several potential prognostic biomarkers like CD44 (Chen et al, 2014), HER2 (Gravalos and Jimeno, 2008), P53 (Goncalves et al, 2011), and E-cadherin (Zhou et al, 2010) have been identified. Especially, CD44 expression is associated with lymph node metastasis (LNM), distant metastasis, TNM stage, and poor prognosis of GC (Chen et al, 2014), as CD44 is a cell surface glycoprotein receptor for hyaluronan acid involved in cell adhesion, migration and metastasis of GC cells (Winder et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Apparently, early diagnosis of its recurrence and metastasis is the biggest challenge in improving the survival of patients with GC. Several potential prognostic biomarkers like CD44 (Chen et al, 2014), HER2 (Gravalos and Jimeno, 2008), P53 (Goncalves et al, 2011), and E-cadherin (Zhou et al, 2010) have been identified. Especially, CD44 expression is associated with lymph node metastasis (LNM), distant metastasis, TNM stage, and poor prognosis of GC (Chen et al, 2014), as CD44 is a cell surface glycoprotein receptor for hyaluronan acid involved in cell adhesion, migration and metastasis of GC cells (Winder et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that most cases of early stage gastric carcinoma can be cured by surgical resection, metastasis contributes to the high rate of mortality in gastric carcinoma [7]. Although numerous immunohistochemical markers such as human epidermal growth factor receptor 2, matrix metallopeptidase-2, and epithelium cadherin have been recognized as biomarkers in other types of cancer, these markers are not commonly used to assess biological behavior and prognosis in gastric cancer because of low levels of sensitivity and specificity [8][9][10][11][12][13]. Therefore, there is an urgent need to identify novel prognostic and predictive biomarkers to improve the diagnosis and clinical management of patients with gastric cancer, which in turn may help to develop more effective treatment strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Many first-line phase II trials have evaluated cetuximab in combination with various chemotherapy regimens [Pinto et al 2007[Pinto et al , 2009Woell et al 2008;Han et al 2009;Kanzler et al 2009;Kim et al 2009;Lordick et al 2010;Moehler et al 2010] showing an ORR in the range of 40-60%, time to progression 5.5-8 months, and OS 9.5-16 months. However, preliminary results of a randomized phase II study showed no clinically significant benefit when cetuximab was added to docetaxel plus oxaliplatin [Richards et al 2011] [Stein et al 2007;Tebbutt et al 2008;Li et al 2010].…”
Section: Targeting Her2mentioning
confidence: 99%